Concentration and Competition: Evidence from Europe and Implications for Policy - Gábor Koltay; Szabolcs Lorincz; Tommaso M. Valletti (Center for Economic Studies and ifo Institute (CESifo), 2022)
The paper provides new evidence on proxy indicators of market power for major European countries. The data shows moderately increasing average industry concentration over the last two decades, a considerably increasing proportion of high concentration industries, and an overall tendency towards oligopolistic structure. Estimates of aggregate profitability also show a sustained increase over the recent decades for European economies. While the academic and policy debate is not settled as to whether the causes of these trends are policy driven or reflect technological improvement, our findings suggest that competition policy is likely to face more challenges as large companies are becoming more common in more and more industries.
Keywords: L10; L40; G34; 330; mergers; antitrust; European Union; concentrations; industries